Baryon junction effects on charmonium production in pp and pPb collisions - Oliveira, Ríchard Terra de (2024)
In this work we study the effects of the proton and $Pb$ internal structure on charmonium production at high multiplicities. To do this, we assume that the nucleon has an Y shape, which means that the effective quarks (quarks + antiquarks + gluons) are in the extremities of the Y, connected by gluon lines. Since the quarks are in the periphery and the gluons are in the center, as $pp$ collisions go from peripheral to more central and then to ultra-central collisions, the interactions change from quark-quark to gluon-gluon. The enhanced growth of $J/\\psi$ occurs because $\\sigma( g + g \\to c + \\bar c) \\gg \\sigma( q + \\bar q \\to c + \\bar c)$. In the $p-Pb$ collisions the enhancement is caused by the high concentration of partons in the center of the nuclei. These effects can explain the growth seen in the data and give support to the Y picture of the proton.